A-122 Verbal Fluency Switching and Clustering Performance in Retired Professional Football Players. (30th August 2021) - Nordberg, Bethany; Lopez-Hernandez, Daniel W; Bueno, Alexis; Victor, Tara L; Saravia, Sarah; Baez, Abril J; Sidhu, Jasman; Munoz, Isabel; Cantu, Robert C; Guskiewicz, Kevin M; Kelly, Daniel F; Swerdloff, Ronald; et al.
Abstract: Introduction: Repeated sports-related concussion has been associated with cognitive deficits, like other forms of traumatic brain injury. Football speed players (FSP; e.g., quarterbacks) are at greater risk of cognitive impairment compared to football non-speed players (FNP). Verbal fluency is typically comprised of two tasks: letter fluency (LF) and semantic fluency (SF). Verbal clustering (production of continuous words belonging to the same category or subcategory) and switching (abandoning an exhausted semantic cluster to a new one in order to produce more words) reflect executive control and strategy use. We examined LF, SF, as well as LF and SF switching and clustering performance in retired FSP, FNP, and healthy comparison (HC) participants. Methods: The sample consisted of 28 HC, 17 retired FSP, and 53 retired FNP. ANOVAs were conducted to determine group differences on LF, SF, switching, and clustering. FSP and FNP did not differ in concussion frequency. Results: We found the HC group outperformed the FSP group in LF, p = 0.042, ηp 2  = 0.07. For SF, the HC and FNP groups outperformed the FSP group, p = 0.013, ηp 2  = 0.09. Furthermore, we found the HC group outperformed both football groups in SF switching, p = 0.000, ηp 2  = 0.17. Conclusion: As expected, the HC group outperformed the FSP group on LF and SF. Also, the FNP group outperformed the FSP group on SF. Interestingly, FSP displayed generally worse performances, supporting the notion that their experience of sub-concussive blows puts them at greater risk for cognitive impairment. Further investigation is needed with larger sample sizes to evaluate SF and other cognitive deficits in the FSP participants.